1998
DOI: 10.1079/bjn19980056
|View full text |Cite
|
Sign up to set email alerts
|

Metal (molybdenum, copper) accumulation and retention in brain, pituitary and other organs of ammonium tetrathiomolybdate-treated sheep

Abstract: 2Ammonium tetrathiomolybdate (TTM) is the treatment of choice for chronic Cu poisoning in sheep and is recommended in Wilson's disease. However, the long-term effects have not been fully evaluated and some evidence questions the long-term safety of the drug. The aim of the present study was to investigate the systemic distribution and retention of Cu and Mo in TTMtreated sheep of different breeds and Cu status. Low-Cu Cambridge sheep were divided into a TTM trial group (3.4 mg/kg, subcutaneously, on three alte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 5 publications
0
25
0
1
Order By: Relevance
“…Although Mo was discovered to accumulate in all organs including the brain and pituitary (Haywood et al, 1998), this study showed that Mo is kept at a relatively low concentration in the different brain regions of goats with a mean concentration of 0.08 ppm without any significant differences between the sexes. Mo in the form of Ammonium tetrathiomolybdate (TTM) is used to treat chronic Cu poisoning in sheep and has been recommended in Wilson's disease, although recent findings question the long term safety of the drug.…”
Section: Discussionmentioning
confidence: 99%
“…Although Mo was discovered to accumulate in all organs including the brain and pituitary (Haywood et al, 1998), this study showed that Mo is kept at a relatively low concentration in the different brain regions of goats with a mean concentration of 0.08 ppm without any significant differences between the sexes. Mo in the form of Ammonium tetrathiomolybdate (TTM) is used to treat chronic Cu poisoning in sheep and has been recommended in Wilson's disease, although recent findings question the long term safety of the drug.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic interrelationship of molybdenum with other trace elements is important when either beneficial or harmful effects of molybdenum compounds are considered. For example, ammonium tetrathiomolybdate can be used in the therapy of Wilson's disease defined as a congenital inability of copper excretion, thus resulting in its accumulation within the body [40].…”
Section: Biomedical Significance Of Molybdenum Compoundsmentioning
confidence: 99%
“…Antiviral, anticoagulant and anticancer activities of these compounds will be also considered [10,12,39]. In addition, it should be mentioned that Haywood et al [40] observed the competition between molybdenum and copper accumulation, a phenomenon of great importance for the treatment of Wilson's disease.…”
Section: Introductionmentioning
confidence: 99%
“…Fodder containing 5 mg Mo kg À1 DM increased xanthine oxidase activity in the liver, renal cortex and serum of growing cattle (Kleczkowski et al 1994). Tetrathiomolybdate has been used successfully against copper intoxication of sheep (Haywood et al 1997). Molybdenum absorption is also inhibited by high levels of dietary sulfate, whereby molybdenum and sulfate compete for similar uptake systems (Mills and Bremner 1980 Molybdenum is absorbed by plants as MoO 2À 4 , though on average only 4 -10 g Mo per hectare are removed from the soil annually by crops.…”
Section: Interactionsmentioning
confidence: 99%